Endothelin-1 is elevated in monocrotaline pulmonary hypertension - Frasch, H Frederick; Marshall, Carol; Marshall, Bryan E (American journal of physiology. Lung cellular and molecular physiology, 1999)
These studies document striking pulmonary vasoconstrictor response to nitric oxide synthase (NOS) inhibition in monocrotaline (MCT) pulmonary hypertension in rats. This constriction is caused by elevated endothelin (ET)-1 production acting on ET receptors. Isolated, red blood cell plus buffer-perfused lungs from rats were studied 3 wk after MCT (60 mg/kg) or saline injection. MCT-injected rats developed pulmonary hypertension, right ventricular hypertrophy, and heightened pulmonary vasoconstriction to ANG II and the NOS inhibitor N -monomethyl-l-arginine (l-NMMA). In MCT-injected lungs, the magnitude of the pulmonary pressor response to NOS inhibition correlated strongly with the extent of pulmonary hypertension. Pretreatment of isolated MCT-injected lungs with combined ET (BQ-123) plus ET (BQ-788) antagonists or ET antagonist alone prevented thel-NMMA-induced constriction. Addition of ET antagonist reversed establishedl-NMMA-induced constriction; ET antagonist did not. ET-1 concentrations were elevated in MCT-injected lung perfusate compared with sham-injected lung perfusate, but ET-1 levels did not differ before and after NOS inhibition. NOS inhibition enhanced hypoxic pulmonary vasoconstriction in both sham- and MCT-injected lungs, but the enhancement was greater in MCT-injected lungs. Results suggest that in MCT pulmonary hypertension, elevated endogenous ET-1 production acting through ET receptors causes pulmonary vasoconstriction that is normally masked by endogenous NO production.